OBJECTIVE AND SUBJECTIVE FACTORS IN THE EMERGENCE OF THE FIRST PERIOD OF THE EASTERN RENAISSANCE (9TH-12TH CENTURIES) (Scientific journal of the Fergana State University, 2025)
In the article, the authors studied the contribution of scientists of medieval Central Asia to the world culture of mankind. The achievements of science, literature, art and philosophy of the early Middle Ages in the East were a necessary link in the chain of historical development of human civilization. It is naturally comparable to the greatest achievements of the geniuses of the European Renaissance. The peculiarity of the Eastern Renaissance before the European one is that it covers a more significant period of history in Central Asia than the Western one, and it began much earlier than in European countries. Many achievements of representatives of the Eastern Renaissance were subsequently studied by representatives of the scientific community and, on their basis, new discoveries were made in various sciences.